Focus and negative concord in hungarian - Bende-Farkas, Ágnes (Proceedings of the Amsterdam Colloquium, 2005)
This paper presents a newly discovered exception to Negative Concord in Hungarian that does not involve double negation. Rather, it is like English it clefts that contain two negative particles that correspond to two instances of negation, in two independent formulae. The paper extends a DRT-based analysis of Hungarian Focus to the simplest cases, mentions some implications for the division of labour between syntax and semantics and suggests a possible method of presupposition accommodation that is required by the more complex cases.